THE EFFECTS OF A COMPREHENSIVE TEACHING PROGRAM ON DRIBBLING AND PASSING DECISION-MAKING AND EXECUTION SKILLS OF YOUNG FOOTBALLERS (Kinesiology, 2017)
The importance of decision-making on what to do and skill execution within sport expertise has been emphasized in many research studies. Thus, the aim of this study was to assess the effect of a 22-session comprehensive teaching program on tactical behavior in agreement with different actions (passing and dribbling) in young footballers. This program was based on the Teaching Games for Understanding (TGfU) model (Bunker & Thorpe, 1982). A quasi-experimental design intervention was developed with nine footballers (U-12) over a 15-week period, which was divided into two phases: pre-intervention (comprised of six sessions and measured during three matches) and intervention (comprised of 22 sessions and measured during 12 matches). Two measures were carried out during the latter phase: an intermediate measure during the First 11 sessions, and a final measure, during the remaining 11 sessions. A total of 2 432 actions were observed (1 793 passes and 639 dribbling actions). Results showed a significant improvement in decision-making and skill execution capabilities after the 22 sessions but not after the first 11 sessions. In addition, differences were found between the two game actions, given that a significant improvement was encountered in both variables of the pass action, but only in the execution variable of the dribbling action. These findings highlight the need to know which type of action is going to be trained (more tactical or technical) in order to adapt the training session methodology. It also seems that, for the teaching program to be effective, it should be applied over a longer timeline of at least 22 sessions.Key words: cognitive processes, young footballers, on-the-ball skills, TGfU, modified games